2021
DOI: 10.2217/lmt-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Use of immune checkpoint inhibitors in patients with solid tumors and pre-existing autoimmune or inflammatory disease: real-world data

Abstract: Aim: Immune checkpoint inhibitors (ICIs) are a cornerstone in cancer treatment but they can induce immune-related adverse events (irAEs). Furthermore, patients with pre-existing autoimmune and/or inflammatory disease (AID) have been excluded from clinical trials. The objective of this study is to evaluate the efficacy and safety of ICIs in patients with cancer and AID. Materials & methods: This is an observational, retrospective study carried out at the Medical Oncology Department of Hospital Universitario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Finally, 12 studies (11-22) met the eligibility criteria, and the selection flowchart is shown in Figure 1. All studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were published in English. The publication dates ranged from 2016 to 2021.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 12 studies (11-22) met the eligibility criteria, and the selection flowchart is shown in Figure 1. All studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were published in English. The publication dates ranged from 2016 to 2021.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Two studies (15,18) were prospective. Eleven studies (11)(12)(13)(14)(16)(17)(18)(19)(20)(21)(22) were multicenter, and the majority of these studies were conducted in the United States, Australia, France, Germany, and Spain. A total of 191 participants were included, with four studies (11,18,19,21) including patients with psoriasis, whereas the remaining eight studies (12-17, 20, 22) included patients with psoriasis and PsA.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations